1986
DOI: 10.1103/physrevlett.57.3277
|View full text |Cite
|
Sign up to set email alerts
|

Fast sound in two-component liquids

Abstract: A new high-frequency and short-wavelength collective mode specific to binary liquid mixtures with large mass difference is observed in a computer simulation of Lio.8Pbo.2 and discussed within the framework of the Mori-Zwanzig formalism. The mode shows linear dispersion in a wave-number regime 0.1 A "* < ^ < 0.6 A~^ but its propagation velocity is higher than the ordinary sound velocity by more than a factor of 3. Its attenuation is only weakly q dependent in contrast to the damping of ordinary sound. In Lio.8P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 5 publications
1
84
0
Order By: Relevance
“…Since the pioneer MD simulation of Na-K liquid alloy 1 the majority of studies have been centered on the alloy Li 4 Pb. In a MD simulation of this system Bosse et al 2 observed the existence of high-frequency peaks in the partial Li-Li dynamic structure factors at rather large wave vectors. These peaks were associated with longitudinal modes that propagate through light particles with a velocity much higher than that of the ordinary sound ͑the so-called ''fast sound''͒.…”
Section: Introductionmentioning
confidence: 98%
“…Since the pioneer MD simulation of Na-K liquid alloy 1 the majority of studies have been centered on the alloy Li 4 Pb. In a MD simulation of this system Bosse et al 2 observed the existence of high-frequency peaks in the partial Li-Li dynamic structure factors at rather large wave vectors. These peaks were associated with longitudinal modes that propagate through light particles with a velocity much higher than that of the ordinary sound ͑the so-called ''fast sound''͒.…”
Section: Introductionmentioning
confidence: 98%
“…So far it has not been finally established what is going on with the high-frequency propagating branch in the long-wavelength limit. Hence, the problem of "fast sound" [7] reported in the literature over almost 20 years is still far from being finally solved. It is not also known what is the role of concentration in the damping of high-frequency branch, how the mass ratio affects the width of hydrodynamic region, how will the dispersion law change by decreasing the concentration of relevant species up to the impurity limit.…”
Section: Introductionmentioning
confidence: 99%
“…On the theoretical side, kinetic theory calculations [18] for two-component fluids with large atomic mass difference, have confirmed the appearance of a collective mode at high frequencies and wave numbers q q h . Moreover, this mode propagated with a phase velocity close to that of the pure light component, which was clearly greater than the hydrodynamic sound velocity, c h , of the two-component system.…”
Section: Introductionmentioning
confidence: 92%
“…It was followed by the CMD results for liquid Li 4 Pb [7], where a new, high-frequency mode, allegedly supported by the light Li atoms only, (the so-called "fast sound") was found. This finding spurred a wealth of experimental [8][9][10][11][12][13], computer simulation [8,[14][15][16][17] and theoretical [18][19][20][21][22] works focused on the investigation of the nature and properties of the collective excitations in liquid binary systems.…”
Section: Introductionmentioning
confidence: 99%